HUBUNGAN ANTARA KONTROL DIRI DAN HARGA DIRI DENGAN PERILAKU KONSUMTIF TERHADAP GADGET PADA SISWA KELAS XII SMAN 8 BOGOR - Nofitriani, Nisrina Nibras (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
This research is a quantitative study that discusses self-control and self-esteem withconsumptive policies on gadgets. The subjects in this study were class 12th grade studentsat state high school 8 Bogor, with a total of 175 samples using Simple Random Samplingtechnique. This study uses 3 scale measuring instruments, namely: consumer measuringscale, self-measuring scale and self-esteem measurement scale. Data analysis usingbivariate showed a positive relationship between self-control and consumptiverelationships with r = 0.175 <0.05. There is a positive relationship between self-esteemand consumptive academic education r = 0.156 <0.05. Based on a multivariateregression test that showed a significant relationship between self-control and self-esteemwith a consumptive relationship with R = 0.176 <0.05 and related to the R Squaredetermination coefficient of 0.031.